Translanguaging in a Chinese university CLIL classroom: Teacher strategies and student attitudes - Zhou, Xiaozhou (Emily); Mann, Steve (Studies in Second Language Learning and Teaching, 2021)
Pedagogical translanguaging has been extensively researched over the past decade. Yet, little is known about the attitudes of students towards this practice. Students constitute an integral part of classroom interactions and their learning process is significantly affected by teachers’ classroom discourse. This action research (AR) study, situated in a Chinese university Content and Language Integrated Learning (CLIL) reading classroom and aided by lesson recordings and two sets of questionnaires, explores the translanguaging strategies employed by the teacher as well as the students’ attitudes to such strategies. Through incorporating feedback collected from students regarding the teacher’s modifications of language use, the study has demonstrated how the teacher mobilizes her full linguistic resources, in the form of translanguaging, to achieve pedagogical outcomes, which eventually leads to the establishment of a mutually beneficial classroom ecology. The study also indicates that advanced EFL learners, highly motivated to improve language proficiency and acquire subject content unanimously reject the traditional monolingual approach to teaching. The findings call for further research into the impact of pedagogical translanguaging on students’ learning process in multilingual classrooms.